EFFECT OF GARLIC AND LICORICE ROOT EXTRACT ON LEAVES MINERAL AND HORMONAL CONTENT OF PEAR TRANSPLANTS - & Al-Rawi, Shakir (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
This research was conducted during the growing season 2015 - 2016 to investigate the response of 2 year’s old transplants of “Othmani” pear cultivar budded on Calleryana root stock to foliar application with licorice root extract at four levels 0 (Li0), 2.5 g.L-1 (Li2.5), 5 g.L-1 (Li5) and 10 g.L-1 (Li10) and garlic extract at four levels, 0 (GA0), 5ml.L-1 (GA5), 10ml.L-1 (GA10) and 20ml.L-1 (GA20) and their interaction in leaves mineral and hormonal content . Each treatment was replicated three times using a factorial experiment using RCBD. The number of trees used was 96 trees. The results showed that the interaction between spraying garlic extract at 20 ml .L-1 combined with licorice root extract at 10 g .L-1 (GA20Li10) gave a high value of leaves nitrogen content at1.35 and 1.83%, potassium content at 2.410 and 2.592%, iron content at 210.3 and 234.5 mg. Kg -1and highest leaves zinc content at18.00 and 20.22 mg. Kg -1 for both seasons, respectively. As well as for hormones, GA20Li10 treatment was given the highest leaves content of IAA at 41.73 and 46.52 μg·g-1and the highest leaves GA3 content with 229.8 and 259.4 μg·g-1 for both seasons respectively. The lowest value of these parameters was found in the control (GA0Li0) treatment.